Oral Nifedipine versus Intravenous Labetalol for Acute Blood Pressure Control in Severe Hypertension of Pregnancy: A Study at Faridpur Medical College Hospital (Faridpur Medical College Journal, 2021)
The first line antihypertensive treatment for severe hypertension of pregnancy includes labetalol, hydralazine, or nifedipine. Rapid but safe blood pressure control allows the definitive treatment, the delivery of baby to be carried out with minimal delay and good maternal and fetal outcomes. This non-randomized clinical trial was performed in Faridpur Medical College Hospital to compare the effectiveness and tolerability of oral nifedipine and intravenous labetalol in the acute control of severe hypertension of pregnancy. Total 50 admitted pregnant women with a viable fetus (>_ 24 weeks of gestation) having severe hypertension were allocated into two groups, Group A: 25 patients receiving oral nifedipine (10 mg), Group B: 25 patients receiving injectable labetalol (with incremental doses: 20, 40, 80mg). Up to 5 doses were tried for each drug at 15 minutes interval until target blood pressure (